Amplified luminescence in organo-curium nanocrystal hybrids. Issue 16 (10th April 2019) - Agbo, Peter; Müller, Alexander; Arnedo-Sanchez, Leticia; Ercius, Peter; Minor, Andrew M.; Abergel, Rebecca J.
Abstract : Amplified luminescence of 248 Cm 3+ doped in a NaGdF4 lattice is achieved through optical pumping of a surface-localized metal chelator, 3, 4, 3-LI(1, 2-HOPO). Abstract : We present the first report of ligand-sensitized, actinide luminescence in a lanthanide nanoparticle host. Amplified luminescence of 248 Cm 3+ doped in a NaGdF4 lattice is achieved through optical pumping of a surface-localized metal chelator, 3, 4, 3-LI(1, 2-HOPO), capable of sensitizing Cm 3+ excited states. The data suggest the possibility of using such materials in theranostic applications, with a ligand-sensitized actinide or radio-lanthanide serving the dual roles of a nuclear decay source for radiotherapeutics, and as a luminescent center or energy transfer conduit to another emissive metal ion, for biological imaging.